EFFICIENCY OF THE INTEGRATED USE OF FERTILIZERS AND GROWTH REGULATORS IN POTATO CULTIVATION - Poliukhovych , М.; Kutsel , Б. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
Field experiments to study the combined use of the Biolan growth stimulator and various rates of mineral fertilizers were conducted in the conditions of the Western region of Ukraine on dark gray podzolized soil during 2023–2024. The research scheme included the following options: 1. Control – without fertilizers; 2 – N60P60K90; 3 – N60P60K90 + PP; 4 – N90P90K120; 5 – N90P90K120 + PP. Fertilizers in the specified rates were applied in spring for cultivation, plant treatment with the Biolan growth regulator was carried out during the budding period, combining it with the application of pesticides to combat pests and plant diseases in joint tank mixtures. It was found that the application of fertilizers and growth regulators had a significant effect on plant height growth and leaf surface formation. The increase in leaf surface area on the N60P60K90 + PP fertilizer option increased by 9.1 thousand m2/ha, and on N90P90K120 + PP fertilizer – 10.9 thousand m2/ha with a leaf surface area of 31.1 thousand m2/ha (control). The complex application of fertilizers and spraying of potato plants during budding with Biolan ensured an increase in tuber yield, which, on average over the years of research was 6.6 t/ha with N60P60K90 fertilizer and 12.8 t/ha with N90P90K120 fertilizer rates with yields according to the fertilizer rates of 29.8 and 38.1 t/ha. The studies also revealed a positive effect of the complex application of fertilizers and growth regulators on the quality indicators of potato tubers. With their combined use, the yield of dry matter and starch per unit area increased significantly and was the highest in the experiment with the N90P90K120 fertilizer level together with the use of Biolan and amounted to 8.87 t/ha of dry matter and 6.25 t/ha of starch. The complex use of fertilizers and the Biolan growth regulator is an effective agricultural measure in improving plant nutrition conditions and increasing potato productivity.